Respective influence of current alcohol consumption and duration of heavy drinking on brain morphological alterations in alcohol use disorder. (9th April 2019) - Rolland, Benjamin; Dricot, Laurence; Creupelandt, Coralie; Maurage, Pierre; De Timary, Philippe
Abstract: Numerous studies have explored the morphological differences of the brain between subjects with alcohol use disorder (AUD) and control subjects, but very few have investigated the impact of the duration of alcohol use disorder (DAD) and current level of alcohol consumption (CAC) within AUD subjects using magnetic resonance imaging (MRI). We compared the morphological MRI of 44 controls and 66 AUD subjects, recruited at the end of a detoxification program. Additional analyses within the AUD group determined which specific alterations were respectively associated with DAD and CAC using: (1) Bonferroni‐corrected multivariable linear regressions to explore the DAD/CAC impact on brain volumes and (2) a general linear model (GLM module of FreeSurfer's Qdec) and Monte Carlo simulation to correct for multiple comparisons ( P < 0.05) to explore the DAD/CAC impact on cortical thickness and volumes. Analyses were adjusted for age and tobacco use. CAC and DAD were significantly correlated (ρ = 0.25, P < 0.0001), and sensitivity analyses were conducted with and without both CAC and DAD included in the same model. While the AUD‐control comparisons globally reproduced preexisting findings, within‐AUD analyses found that CAC was inversely correlated with cortical thickness and gray matter volume in a bilateral dorsal band of the temporal lobe, including the fusiform and parahippocampal gyri. For DAD, only a left and more ventral temporal band that partially overlapped the CAC‐associated area was found in cortical thickness analyses. No significant volumetric result was reached after a Bonferroni correction. CAC and, to a lesser extent, DAD were thus associated with specific, though partially overlapping, temporal surface‐based signatures. Abstract : Current level of alcohol consumption (CAC) was inversely correlated with cortical thickness and gray matter volume in a bilateral dorsal band of the temporal lobe while the duration of alcohol use disorder was inversely correlated with only a left and more ventral temporal band that partially overlapped the CAC.